Strategies to Enhance Students' Entrepreneurial Spirit Through Caring Economics Entrepreneurship Education - Siti Nurul Aini Hidayah; Mohammad Dasuki; Syarifatul Marwiyah (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
This study aims to examine the impact of implementing a caring economics-based Project Based Learning model on increasing students' entrepreneurial interest. The method used was a quasi-experimental one involving students as research subjects. The learning process was carried out through several stages, including environmental observations, interviews with business actors, report preparation, designing creative business ideas, and reflection on activities. Data analysis was carried out using a difference test to determine significant changes before and after the treatment. The results showed an increase in students' entrepreneurial interest after participating in the learning. The number of respondents with a high interest category increased from 10% to 30%, the medium category increased from 30% to 56%, while the low category decreased drastically from 60% to 14%. The average entrepreneurial interest score also increased from 4.27 before the treatment to 5.60 after, with a significance level of 0.000 (<0.05). These findings prove that the caring economics-based entrepreneurship learning model is effective in fostering interest, developing creative and innovative characters, and strengthening students' readiness to enter the business world.